Coherent Perfect Absorber Based on Antisymmetric Metasurface With Gain Material - Ming Chen; Chen Chen; Shijie Deng; Chongyun Wang; Houquan Liu; Chuanxin Teng; Yu Cheng; Hongyan Yang; Ronghui Xu; Hongchang Deng; Libo Yuan (IEEE Photonics Journal)
In this paper, we proposed a two ports coherent perfect absorber based on antisymmetric metasurface with gain material which is able to effectively regulate the absorption of the coherent incident wave under the condition of unequal incident intensities. This design overcomes the limitation that exists in the previous coherent controller which can only be applied to coherent light of equal intensity without gain material. In the proposed absorber, the metal strips of different lengths are arranged in an antisymmetric manner on the interlayer, a gain material layer is introduced to regulate the unequal intensity coherent light and the electromagnetic response mode which can be selectively strengthened and weakened by modulating the phase difference between two incident waves, and a high coherent absorption under the condition of asymmetric incident wave can be realized. Results show that the proposed absorber achieve coherent perfect absorption at the frequency of 15.25 THz and 17.75 THz, which can change the total absorption in the range from 27.41% to 98.55%, and from 27.55% to 97.88%, respectively. This paper may serve as an important tool for all-optical information transmission and data processing.